Kontakty Niemieckiego Towarzystwa Polityki Zagranicznej (DGAP) z Polskim Instytutem Spraw Międzynarodowych (PISM) w latach sześćdziesiątych XX wieku - Świder, Małgorzata (Rocznik Polsko-Niemiecki, 2019)
DGAP’s relationship with PISM dates back to the early 1960s and was basically limited to the exchange of literature. Along with the change in the policy of East Germany, as well as the process of reaching a consensus in Polish-German relations, the importance of both institutes as an additional platform for co‑operation increased. This process was affected by both the internal situation in both countries and the development of the international situation. The signing of the Treaty of Warsaw in December 1970 opened new opportunities for co‑operation between the two institutes.